Investigating the Impact of Cognitive-behavioral Stress Management on Adjustment among Females with Breast Cancer - Jamshidi, Farkhondeh; Shayan, Arezoo; Sattari, Mahtab (Current Women's Health Reviews, 2022)
Background and aim: This study aimed to investigate the effect of cognitive-behavioral stress management (CBSM) on adjustment among females with breast cancer. Materials and Methods: This randomized clinical trial study was conducted on 104 women with breast cancer who visited Hamedan Imam Khomeini Clinic between Feb 3 and Oct 26, 2016, and met the inclusion criteria. The inclusion criteria included being 20 to 60 years old, being married, and having grade 1-3 breast cancer with a history of recent surgery. The subjects were randomly assigned to two groups of 52 subjects, using a permuted block size of 4. The intervention group participated in 4 sessions of CBSM, each 90 minutes long, for a duration of 4 weeks. Data collection was done using a demographic information questionnaire and Bell adjustment questionnaire. The statistical analyst remained unaware of the intervention assignment. Data analysis was done using descriptive statistics, paired t-test, and repeated measures ANOVA. Results: There was a significant difference in the mean scores of the total adjustment (P = 0,0001) between the two groups after the intervention. Each variable was calculated three times, prior to the intervention, immediately after and 2 weeks after the intervention. Regardless of the time of measurement, there was a significant difference in the mean score of total adjustment between the two groups (P = 0.0001). Conclusion: The cognitive-behavioral stress management program improved the adjustment immediately and 2 weeks after the intervention was done among women with breast cancer. This method can be implemented as a complementary approach along with medical therapies provided by oncology centers.
Keywords: breast cancer